Factor Analysis Of Product Quality, Service Quality, And Corporate Image Towards Customer Loyalty Through Customer Satisfaction On CV Vins Cahaya Sukses Customers In Pekanbaru - Wilbert Roderick Tanaldo; Yanuar Dananjaya; Oliandes Sondakh (Jurnal Ekonomi, 2024)
The results obtained by product quality has a significant effect on ap customer satisfaction, service quality has a significant effect on customer satisfaction, corporate image has a significant effect on customer satisfaction, product quality has a significant effect on customer loyalty, service quality has a significant effect on customer loyalty, corporate image has a significant effect on customer loyalty and customer satisfaction has a significant effect on customer.